Divergent SARS-CoV-2-specific T cell responses in intensive care unit workers following mRNA COVID-19 vaccination - Salgado Del Riego, Estefanía; Saiz, María Laura; Corte-Iglesias, Viviana; Leoz Gordillo, Blanca; Martin-Martin, Cristina; Rodríguez-Pérez, Mercedes; Escudero, Dolores; Lopez-Larrea, Carlos; Suarez-Alvarez, Beatriz (Frontiers in Immunology, 2022)
The cellular immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in response to full mRNA COVID-19 vaccination could be variable among healthy individuals. Studies based only in specific antibody levels could show an erroneous immune protection at long times. For that, we analyze the antibody levels specific to the S protein and the presence of SARS-CoV-2-specific T cells by ELISpot and AIM assays in intensive care unit (ICU) workers with no antecedents of COVID-19 and vaccinated with two doses of mRNA COVID-19 vaccines. All individuals were seronegative for the SARS-CoV-2 protein S before vaccination (Pre-v), but 34.1% (14/41) of them showed pre-existing T lymphocytes specific for some viral proteins (S, M and N). One month after receiving two doses of COVID-19 mRNA vaccine (Post-v1), all cases showed seroconversion with high levels of total and neutralizing antibodies to the spike protein, but six of them (14.6%) had no T cells reactive to the S protein. Specifically, they lack of specific CD8+ T cells, but maintain the contribution of CD4+ T cells. Analysis of the immune response against SARS-CoV-2 at 10 months after full vaccination (Post-v10), exhibited a significant reduction in the antibody levels (p<0.0001) and protein S-reactive T cells (p=0.0073) in all analyzed individuals, although none of the individuals become seronegative and 77% of them maintained a competent immune response. Thus, we can suggest that the immune response to SARS-CoV-2 elicited by the mRNA vaccines was highly variable among ICU workers. A non-negligible proportion of individuals did not develop a specific T cell response mediated by CD8+ T cells after vaccination, that may condition the susceptibility to further viral infections with SARS-CoV-2. By contrast, around 77% of individuals developed strong humoral and cellular immune responses to SARS-CoV-2 that persisted even after 10 months. Analysis of the cellular immune response is highly recommended for providing exact information about immune protection against SARS-CoV-2.